2016
DOI: 10.1111/andr.12175
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal phthalate exposure: epigenetic changes leading to lifelong impact on steroid formation

Abstract: SUMMARYEndocrine disruptors (ED) are environmental pollutants that mimic endogenous hormonal signals. Exposure to EDs during fetal and early life is a public health concern because these are periods characterized by high cellular plasticity that influence the physiology and development of disease later in life. Phthalates are plasticizers used in the industry to manufacture polyvinyl chloride products and several consumer products. Di(2-ethylhexyl) phthalate (DEHP) is one of the most produced plasticizers; it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 114 publications
2
28
0
Order By: Relevance
“…The negative relationship observed between PPARA methylation and SDEHP is particularly notable. In addition to being one of the most commonly identified EDCs in the US population [45], observed changes in DNA methylation and expression in adult rats resulting from in utero SDEHP exposure have raised speculation that the PPAR pathway, and specifically PPARA, may participate in epigenetic disruption [46]. The findings from the present study support this hypothesis, as human PPARA promoter was inversely associated with SDEHP levels.…”
Section: Discussionsupporting
confidence: 75%
“…The negative relationship observed between PPARA methylation and SDEHP is particularly notable. In addition to being one of the most commonly identified EDCs in the US population [45], observed changes in DNA methylation and expression in adult rats resulting from in utero SDEHP exposure have raised speculation that the PPAR pathway, and specifically PPARA, may participate in epigenetic disruption [46]. The findings from the present study support this hypothesis, as human PPARA promoter was inversely associated with SDEHP levels.…”
Section: Discussionsupporting
confidence: 75%
“…However, the results were consistent with previous studies that showed that DEHP had antiandrogenic and estrogenic effect in children [15, 40]. These children should be followed to investigate the effects of exposure to phthalate-tainted foodstuffs on children’s health [41]. Second, the range of the children’s age was wide (mean = 5.48 years; range = 1 to approximately 11.6 years) in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…In males, adrenal androgens are far surpassed by androgens produced by the testes, so effects on the adrenal gland may not be evident. Animal studies have demonstrated that the adrenal gland is indeed a target for in utero DEHP exposure, with females being more sensitive to exposure than males and effects that last into adulthood (Martinez-Arguelles and Papadopoulos 2016). One hypothesis for how this may occur is through changes in fetal epigenetic programming (Martinez-Arguelles and Papadopoulos 2016).…”
Section: Discussionmentioning
confidence: 99%